Camellia sinensis methanolic leaves extract: Phytochemical analysis and anticancer activity against human liver cancer cells. - Demiana H Hanna; Ahlam K Al-Atmani; Aljazi Abdullah AlRashidi; E El Shafee (PLoS ONE)
Background The study's primary goal is to ascertain whether there is a relationship between the processed green tea methanolic extract's (GTME) phytochemical components and its potential effectiveness against human liver cancer cells. The GTME's phytochemical composition was identified using gas chromatography-mass spectrometry, and the extract's capacity to lower cellular proliferation and cause apoptosis in HepG2 cancerous liver cell lines was checked. Results The findings of the gas chromatography-mass chromatogram showed that GTME included bioactive antioxidants and anticancer substances. Additionally, utilizing the MTT, comet assay, and acridine assay, GTME revealed a selective cytotoxic impact with a significant IC50 value (27.3 µg/ml) on HepG2 cells without any harmful effects on WI-38 healthy cells. Also, compared to untreated cells, the extract-treated HepG2 cells had an upsurge in the proportion of cells that have undergone apoptosis and displayed a comet nucleus, which is a sign of DNA damage. In addition, HepG2 cells treated with GTME revealed a stop in the G1 phase and sub-G1 apoptotic cells (37.32%) in a flow cytometry analysis. Furthermore, reactive oxygen species were shown to be responsible for HepG2 apoptosis, and the tested extract significantly reduced their levels in the treated cells. Lastly, compared to untreated cells in treated HepG2 cells, GTME significantly changed protein expression levels linked with cell cycle arrest in the G1 phase and apoptosis. Conclusion These findings provided information about the processes through which the GTME inhibited the growth of HepG2. Therefore, it has potential as an effective natural therapy for the treatment of human liver cancer. However, to validate these findings, animal models must be used for in vivo studies.